Hidden discourses and implications of "at-risk’"and "underprepared" labels in a South African university: Seeking humane alternatives - Ravhuhali, F.; Mboweni, H. F.; Nendauni, L. (South African Journal of Higher Education, 2026)
This article explores the hidden discourses and far-reaching implications associated with labelling students as “at-risk” and “underprepared” in a South African university. By unpacking the criteria, exploring the consequences, and scrutinising systemic biases, we provide a comprehensive understanding of the multifaceted dynamics surrounding these two labels. We adopted theory triangulation with Labelling theory as the central theoretical framework operationalised through Mill’s Millian theory of names, Frege’s Sense-based theory of names, and Russell’s Descriptive theory of names. We employed qualitative methods, encompassing questionnaires and literature reviews, and thematic analysis was utilised for data analysis. Findings reveal that “at-risk” and “underprepared” labels are used loosely without due consideration of the variety of contextual, socio-economic, and educational backgrounds of the students. Through this article, we advocate for dialogue among university teachers to support all students and propose new terms to describe students who require extra support. For instance, we suggest names such as “Students in Transition” (SIT) or “Students on a Developmental Pathway” (SDP). In its entirety, this article highlights the need for more inclusive and culturally sensitive naming in higher education as more humane alternatives.